Twenty-four-hour National Institute of Health Stroke Scale predicts short- and long-term outcomes of basilar artery occlusion after endovascular treatment - Chen, Jing; Liu, Shuai; Wu, Mingchao; Dai, Ling; Wang, Jie; Xie, Weihua; Peng, Yuqi; Mu, Jinlin; Yang, Shunyu; Ran, Jinbo; Zhang, Jian; Niu, Wenshu; et al. (Frontiers in Aging Neuroscience, 2022)
Background: To evaluate early surrogate for short- and long-term outcomes of patients with basilar artery occlusion (BAO) after endovascular treatment (EVT) in daily clinical routine. Methods: Patients with endovascular treatment for acute basilar artery occlusion study registry with the 24-h National Institute of Health Stroke Scale (NIHSS), and clinical outcomes documented at 90 days and 1 year were included. The NIHSS admission, 24-h NIHSS, NIHSS delta and NIHSS percentage change, binary definitions of early neurological improvement (ENI; improvement of 4/ [common ENI]/8 [major ENI]/10 [dramatic ENI]) NIHSS points were compared to predict the favorable outcome and mortality at 90 days and 1 year. The primary outcome was defined as favorable if the modified Rankin Scale (mRS) score was 0–3 at 90 days. Results: Of the 644 patients treated with EVT, the 24-h NIHSS had the highest discriminative ability for favorable outcome prediction (receiver operator characteristics [ROC]NIHSS 24 h area under the curve [AUC]: 0.92 [0.90–0.94]) at 90 days and 1 year (ROCNIHSS 24 h AUC: 0.91 [0.89–0.94]) in comparison to the NIHSS score at admission (ROCNIHSS admission AUC at 90 days: 0.73 [0.69–0.77]; 1 year: 0.74 [0.70–0.78]), NIHSS delta (ROCΔNIHSS AUC at 90 days: 0.84 [0.81–0.87]; 1 year: 0.81 [0.77–0.84]), and NIHSS percentage change (ROC%change AUC at 90 days: 0.85 [0.82–0.89]; 1 year: 0.82 [0.78–0.86]). Conclusions: The 24-h NIHSS with a threshold of ≤23 points was the best surrogate for short- and long-term outcomes after EVT for BAO in clinical routine.